Odpowiedzi

2010-02-24T19:38:07+01:00
A)3(x-1)-2 dla x=4,2
3x-3-2=3x-5=3*4,2-5=12,6-5=7,6

b)2(y+6)-4(y-6) dla y=½
2y+12-4y+24=-2y+36=-2*1/2+36=-1+36=35

c)3(a-8)-(5-2a) dla a=-0,5
3a-24-5+2a=5a-29=5*(-0,5)-29=-2,5-29=-31,5

d)4(x-y) -(-x+y) dla x=trzy drugie, y=-1
4x-4y+x-y=5x-5y=5*3/2-5*(-1)=15/2+5=7,5+5=12,5
1 5 1
2010-02-24T19:39:49+01:00
A)3(x-1)-2 dla x=4,2
3(4,2-1)-2 = 3*3,2-2 = 9,6-2 = 7,6

b)2(y+6)-4(y-6) dla y=½
2*6½-4*(-5½) = 13+22 = 35

c)3(a-8)-(5-2a) dla a=-0,5
3*(-8,5)-(5+1) = -25,5-6 = -31,5

d)4(x-y) -(-x+y) dla x=trzy drugie, y=-1
4(3/2 + 1)-(-3/2-1) = 10+2,5 = 12,5
2010-02-24T19:41:39+01:00
A)3(4.2-1)-2=3(3.2)-2=9.6-2=7,6
b)2(½+6)-4(½-6)=2×6,5-4×(-5,5)=13+22=35
c)3(-½-8)-(5-2×(-½))=3×(-8.5)-6=25,5-6=31,5
d)4(³/₂+1)-(-³/₂-1)=10+2.5=12,5